The challenge of recruitment for neurotherapeutic clinical trials in spinal cord injury - Blight, Andrew R.; Weidner, Norbert (Spinal cord, 2019)
Narrative review by individuals experienced in the recruitment of participants to neurotherapeutic clinical trials in spinal cord injury (SCI). To identify key problems of recruitment and explore potential approaches to overcoming them. Published quantitative experience with recruitment of large-scale, experimental neurotherapeutic clinical studies targeting central nervous system and using primary outcome assessments validated for SCI over the last 3 decades was summarized. Based on this experience, potential approaches to improving recruitment were elicited from the authors. The rate of recruitment has varied between studies, depending on protocol design and other factors, but particularly inclusion/exclusion criteria. The recruitment rate also ranged over an order of magnitude between individual centers in a given study. In older multicenter studies, average recruitment rate was approximately one person per study center per month. More recent trials experienced lower rates of recruitment and potential reasons for this trend were examined. The current roles and potential of various stakeholder organizations in addressing problems of recruitment were explored. In addition, recent developments in methodology may help reduce the number of subjects required for well-powered studies. Several approaches are emerging to improve clinical trial design, efficacy outcome measures, and quantifiable surrogate markers, all of which should reduce the number of participants required for adequate statistical power. There is a growing sense of cooperation between various stakeholders but more should be done to bring together consumer and provider groups to improve recruitment and the effectiveness and relevance of neurotherapeutic clinical trials.
Gesehen am 25.06.2020